Outcome measures for assessing the effectiveness of non-pharmacological interventions in frequent episodic or chronic migraine: a Delphi study. Issue 2 (12th February 2020) - Luedtke, Kerstin; Basener, Annika; Bedei, Stephanie; Castien, Rene; Chaibi, Aleksander; Falla, Deborah; Fernández-de-las-Peñas, Cesar; Gustafsson, Mirja; Hall, Toby; Jull, Gwen; Kropp, Peter; Madsen, Bjarne K; et al.
Abstract : Objectives: The aim of this Delphi survey was to establish an international consensus on the most useful outcome measures for research on the effectiveness of non-pharmacological interventions for migraine. This is important, since guidelines for pharmacological trials recommend measuring the frequency of headaches with 50% reduction considered a clinically meaningful effect. It is unclear whether the same recommendations apply to complementary (or adjunct) non-pharmacological approaches, whether the same cut-off levels need to be considered for effectiveness when used as an adjunct or stand-alone intervention, and what is meaningful to patients. Setting: University-initiated international survey. Participants: The expert panel was chosen based on publications on non-pharmacological interventions in migraine populations and from personal contacts. 35 eligible researchers were contacted, 12 agreed to participate and 10 completed all 3 rounds of the survey. To further explore how migraine patients viewed potential outcome measures, four migraine patients were interviewed and presented with the same measurement tools as the researchers. Procedures: The initial Delphi round was based on a systematic search of the literature for outcome measures used in non-pharmacological interventions for headache. Suggested outcome measures were rated by each expert, blinded towards the other members of the panel, for its usefulness on a 5-point Likert scale ranging from definitely not useful to extremely useful. Results were combined using median values and IQRs. Tools rated overall as definitely or probably not useful were excluded from subsequent rounds. Experts further suggested additional outcome measures that were presented to the panel in subsequent rounds. Additionally, experts were asked to rank the most useful tools and provide information on feasible cut-off levels for effectiveness for the three highest ranked tools. Results: Results suggest the use of the Migraine Disability Assessment (MIDAS), Headache Impact Test (HIT-6) and headache frequency as primary outcome measures. Patient experts suggested the inclusion of a measure of quality of life and evaluation of associated symptoms and fear of attacks. Conclusions: Recommendations are for the use of the MIDAS, the HIT-6 and headache frequency, in combination with an outcome measure for quality of life. Associated symptoms and fear of attacks should also be considered as secondary outcomes, if relevant for the individual target population. The cut-off level for effectiveness should be lower for non-pharmacological interventions, especially when used as an adjunct to medication. Trial registration number: German Register of Clinical Trials (DRKS00011777)